ANALISIS YURIDIS PENOLAKAN EKSEKUSI PUTUSAN ARBITRASE INTERNASIONAL (Studi Kasus: Putusan Mahkamah Agung Nomor 808 K/Pdt.Sus/2011 Dalam Perkara Antara PT. Direct Vision Melawan Astro Group Malaysia) - Junandar Indra Tongam Panggabean; Suhaidi Suhaidi; Jelly Leviza; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT PT. Direct Vision applied a request for rejecting the execution on the Rulings of SIAC in 2010 because of the violation against public order. However, the Central Jakarta District Court and the Supreme Court refused the request for rejecting the execution on the ruling of SIAC in 2010 in Indonesia. Legal provision which regulates the rejection for the execution on the International Arbitration decision according to UUA, APS, and new York 1958 convention permits that the request can be filed to the Court in the petitioner’s country, but the cancelation can only be filed in the country where the decision is made. The main reason for the panel of judges to refuse the request for execution on SIAC decisions in 2010 was because PT. Ayunda Prima Mitra simultaneously filed a complaint about illegal action in the South Jakarta District Court against Astro Group Malaysia. It is recommended that UUA and APS should set the period of the International Arbitration registration, the reasons for rejecting the execution on the International Arbitration Decisions should not be mixed with the reasons for rejecting and canceling, and PT. Direct Vision should wait for the decision to execute from the South Jakarta District Court.   Keywords: International Arbitration, Public Order